Internalisasi Suara Demokrasi dalam Penguatan P5 Sebagai Upaya Meningkatkan Civic Participation Peserta Didik di SMPN 15 Bandung: Penelitian - Mariana Magdalena Sihole; Rahmat; Nisrina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study is motivated by the urgency of democratic education in shaping students’ character to become active, critical, and responsible citizens. The research aims to describe the forms of internalizing the voice of democracy in the Strengthening the Pancasila Student Profile Project (P5), identify students’ perceptions of the importance of democratic participation, and analyze its impact on enhancing civic participation at SMPN 15 Bandung. This study employs a descriptive qualitative method with a case study approach and utilizes in-depth interviews, participatory observation, and documentation techniques for data collection. The findings reveal that democratic values are internalized holistically through P5 activities, allowing students to gain direct experience in deliberations, class discussions, campaigning, and the student council election. Students demonstrated improved understanding of democratic principles, increased confidence in expressing opinions, and active involvement in collective decision-making processes. The study concludes that P5’s Voice of Democracy theme effectively fosters civic participation that is substantive rather than symbolic. The implication is that P5 serves as a transformative and relevant character education strategy. It is recommended that such a model be expanded to other secondary schools to promote a more participatory, democratic, and values-based educational environment.